2002
DOI: 10.1086/338784
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Patients with Pulmonary Tuberculosis: Clinical and Molecular Epidemiologic Factors

Abstract: Using restriction fragment-length polymorphism data, we conducted a retrospective cohort study of 139 adult patients with pulmonary tuberculosis to investigate the clinical impact of Mycobacterium tuberculosis infection with a clustered isolate. The cumulative all-cause mortality rate during treatment was 21%. Patients with clustered DNA fingerprint patterns had a reduced risk of death, compared with patients with unique patterns (hazard ratio [HR], 0.5; 95% confidence interval [CI], 0.2-1.1), but this finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 36 publications
5
77
1
1
Order By: Relevance
“…A number of studies from the pre-HIV era or from low HIV incidence regions have found that co-morbid medical conditions, which are likely to be common among the elderly in Thailand, are potent risk factors for death during TB treatment. The list of such conditions is long, including: congestive heart failure (Dewan et al 2004), chronic obstructive lung disease or silicosis (Xie et al 2001;Oursler et al 2002;Dewan et al 2004), cirrhosis (Garcia-Garcia Mde et al 2002;Walpola et al 2003), diabetes (Fielder et al 2002;Oursler et al 2002), renal failure (Rao et al 1998;Xie et al 2001;Walpola et al 2003), low body weight and under-nutrition (Cauchie et al 1988;Rao et al 1998;Garcia-Garcia Mde et al 2002;Santha et al 2002;Walpola et al 2003) and cancer (Xie et al 2001;Dewan et al 2004). Another possible explanation for the association between age and TB death could be delayed TB diagnosis, which many studies have found is a risk factor for death in HIV-uninfected patients (Enarson et al 1978;Allan et al 1981;Bandele & Olude 1985;Cauchie et al 1988;Naalsund et al 1994;Hooi & Goh 1995;PablosMendez et al 1996;Olle-Goig 2000).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies from the pre-HIV era or from low HIV incidence regions have found that co-morbid medical conditions, which are likely to be common among the elderly in Thailand, are potent risk factors for death during TB treatment. The list of such conditions is long, including: congestive heart failure (Dewan et al 2004), chronic obstructive lung disease or silicosis (Xie et al 2001;Oursler et al 2002;Dewan et al 2004), cirrhosis (Garcia-Garcia Mde et al 2002;Walpola et al 2003), diabetes (Fielder et al 2002;Oursler et al 2002), renal failure (Rao et al 1998;Xie et al 2001;Walpola et al 2003), low body weight and under-nutrition (Cauchie et al 1988;Rao et al 1998;Garcia-Garcia Mde et al 2002;Santha et al 2002;Walpola et al 2003) and cancer (Xie et al 2001;Dewan et al 2004). Another possible explanation for the association between age and TB death could be delayed TB diagnosis, which many studies have found is a risk factor for death in HIV-uninfected patients (Enarson et al 1978;Allan et al 1981;Bandele & Olude 1985;Cauchie et al 1988;Naalsund et al 1994;Hooi & Goh 1995;PablosMendez et al 1996;Olle-Goig 2000).…”
Section: Discussionmentioning
confidence: 99%
“…9 HIV infection has also been associated with an increased risk of death during TB treatment in the United States and other industrialized countries. [10][11][12][13][14] Low CD4 Ăž T-lymphocyte count (<200 cells=mm 3 ), previous AIDSdefining illness, multi-drug-resistant TB, 15,16 the presence of extrapulmonary TB (especially meningitis), 17 and a history of injection drug use 18 have all been associated with increased mortality in TB=HIV coinfected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Three case-control studies comparing DM/TB and non-diabetic TB patients from Iran, Saudi Arabia, and Turkey showed no significant association between DM and the risk of MDR-TB [27][28][29]. Similarly, cross-sectional studies in Iran, Turkey, and Taiwan have reported no association between DM and MDR-TB [29][30][31].…”
Section: Discussionmentioning
confidence: 99%